FRP rib with composite coating as well as preparation method and application of FRP rib

By applying a composite coating of powder and resin with volcanic ash activity on the FRP ribs, the problems of corrosion and interface debonding in seawater and sea sand concrete are solved, and the efficient application and long-term stability of the FRP ribs in marine environments are achieved.

CN119843827APending Publication Date: 2025-04-18GUANGXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510058302.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18

Smart Images

  • Figure CN119843827A_ABST
    Figure CN119843827A_ABST
Patent Text Reader

Abstract

The invention provides an FRP (Fiber Reinforced Plastic) rib with a composite coating as well as a preparation method and application of the FRP rib. After the FRP rib passes through the resin coating, the powder with the volcanic ash activity is used for wrapping, so that the resin coating surface of the FRP rib is uniformly covered with the powder, and finally the powder-resin composite coating FRP rib with the volcanic ash activity is formed. According to the technical method for enhancing the durability and the interface performance of the FRP rib in the concrete structure, the corrosion resistance of the FRP rib in the concrete under the high-alkalinity environment is enhanced, and the interface bonding performance between the FRP rib and the concrete is enhanced compared with a traditional resin coating; the method has the advantages of simple process flow, industrial production, easiness in popularization and lower cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an FRP bar with a composite coating, a preparation method and application thereof. Background Art

[0002] In recent years, the pace of marine and coastal engineering construction has accelerated. The use of traditional freshwater river sand and other construction materials needs to be transported from inland, which is costly. Therefore, the development of construction materials that can be obtained locally has become an urgent issue. Studies have shown that the mechanical properties of seawater sand concrete (SWSC) are not significantly different from those of ordinary concrete, so it is considered a viable alternative to traditional freshwater and river sand. However, the use of seawater, sea sand or concrete buildings in marine environments will introduce chloride ions (Cl - ) and sulfate ions (SO4 2- ) and other corrosive elements, especially Cl - and SO4 2- When it accumulates on the surface of the steel bar to a critical concentration, it will cause the steel bar to become dull and rust, seriously endangering the safety and durability of the building.

[0003] Fiber Reinforced Polymer Bar (FRP bar for short) is considered to be an ideal substitute for steel bars in marine engineering due to its high strength-to-weight ratio (density is only 1 / 5 to 1 / 4 of steel, while strength is generally much higher than steel), good fatigue performance, electrical insulation, adjustable material properties, and especially excellent corrosion resistance in marine environments. However, its application is limited by the corrosion of FRP bars in the alkaline environment of SWSC and the debonding problem between the bar and concrete. In past studies, marine anticorrosion material science has been committed to developing coatings with super-hydrophobic and self-cleaning properties. If these anticorrosion coatings are directly applied to FRP bars, it will undoubtedly weaken the interfacial bonding between them and SWSC, leading to the risk of insufficient building bearing capacity and increased construction costs.

[0004] Therefore, it is urgent to improve the corrosion of FRP bars in SWSC applications and the easy debonding of the interface between FRP bars and concrete. Summary of the invention

[0005] The present invention aims to provide an FRP bar with a composite coating, a preparation method and an application thereof, and the durability and interface performance of the FRP bar with a composite coating in a concrete structure. As an ideal substitute for steel bars in SWSC, in order to solve the typical problems of alkali corrosion and interface debonding between FRP bars and concrete in SWSC applications, the present invention develops a composite coating of powder and resin with volcanic ash activity to coat the FRP bars, thereby achieving corrosion resistance of the FRP bars and enhancing the bonding performance between the FRP bars and concrete.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing an FRP bar with a composite coating, comprising the following steps:

[0008] Mixing a thermosetting resin, a resin curing agent or a resin initiator to obtain a resin coating;

[0009] Applying resin coating on the surface of FRP reinforcement;

[0010] The powder with volcanic ash activity is coated on the surface of the resin coating, and solidified to form a composite coating, thereby obtaining an FRP bar with the composite coating.

[0011] Preferably, the powder having pozzolanic activity includes at least one of silica ash, fly ash, metakaolin and slag powder.

[0012] Preferably, the thermosetting resin includes at least one of unsaturated polyester, vinyl ester, epoxy resin, phenolic resin, bismaleimide resin, and polyimide resin;

[0013] And / or, the resin initiator includes at least one of methyl ethyl ketone peroxide, dimethyl aniline, and diethyl aniline;

[0014] And / or, the resin curing agent includes at least one of diethylenetriamine and triethylenetetramine.

[0015] Preferably, the mass ratio of the thermosetting resin, the resin curing agent or the resin initiator is (1-3):(1-3).

[0016] Preferably, the FRP bar includes any one of basalt fiber reinforced composite bar, carbon fiber reinforced composite bar, glass fiber reinforced composite bar and aramid fiber reinforced composite bar.

[0017] Preferably, the D50 particle size of the silica fume is 0.9-1.2 μm; the silica fume comprises the following components in mass fractions:

[0018] SiO2 97.30%, CaO 0.30%, Al2O3 0.40%, SO3 0.83%, MgO 0.21%, K2O 0.26%, and the balance are inevitable impurities.

[0019] Preferably, the mass of the powder having volcanic ash activity is 2.5-4% of the mass of the resin coating.

[0020] Preferably, the curing temperature is 20 to 50°C;

[0021] The thickness of the composite coating is 0.25 to 0.35 mm;

[0022] In a second aspect, the present invention further provides an FRP bar with a composite coating, which is prepared by the preparation method.

[0023] In a third aspect, the present invention also provides an FRP bar with a composite coating prepared by the preparation method or the use of the FRP bar with a composite coating in preparing concrete.

[0024] The FRP bar with composite coating and its preparation method and application of the present invention have the following beneficial effects compared with the prior art:

[0025] 1. The preparation method of the FRP bar with composite coating of the present invention is based on the thermosetting resin coating, and by introducing the powder with volcanic ash activity to cover, the active ingredients in the volcanic ash active powder react with the calcium hydroxide produced by the hydration of cement clinker in the concrete to generate low-alkalinity calcium silicate hydrate (CSH) and calcium aluminate hydrate, and at the same time promote the early hydration of cement near the interface through the nucleus effect, and enhance the compactness and interface bonding performance between the FRP bar and the concrete through the micro-aggregate filling effect and the particle morphology effect; the enhanced design of the corrosion resistance and interface bonding performance of the FRP bar material system in the concrete structure is realized, and the durability of the FRP bar in the concrete structure is effectively improved. In the specific embodiment of the present invention, through the comparative study of the durability test of the uncoated, single resin coated BFRP bar and the silica fume-resin composite coated BFRP bar at 25°C for 360 days, it is found that at the age of 360 days, the performance of the silica fume-resin composite coated BFRP bar only decreases by 8.8%, while the uncoated and resin coated ones decrease by 30.3% and 12.7%, respectively. More prominently, at 360 days, the performance of the silica fume-resin composite coating was 31.6% higher than that of the uncoated one and 4.8% higher than that of the resin coating. In addition, by testing the interfacial bonding strength of BFRP bar concrete specimens immersed in 45°C simulated seawater at different ages, it was found that after 270 days of immersion test, the performance of the BFRP bar with the silica fume-resin composite coating was 1.67% higher than the initial value, while the uncoated and resin coatings decreased by 16.68% and 9.39%, respectively. More prominently, at 270 days, the performance of the silica fume-resin composite coating was 19.32% higher than that of the uncoated one and 24.64% higher than that of the resin coating. In summary, the technical method of enhancing the durability and interfacial performance of FRP bars in concrete structures of the present invention not only provides a new way for the high-value utilization of industrial solid waste, but also has important practical significance for the construction of marine or coastal engineering. Through material composite design, the comprehensive improvement of material durability and interfacial bonding performance is achieved, providing a solution with reference value for the development of FRP bars in seawater and sea sand concrete structure engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 The physical pictures are of the BFRP bar with composite coating prepared in Example 1, the BFRP bar with resin coating prepared in Comparative Example 1, and the BFRP bar (with a diameter of 8 mm) without any treatment;

[0028] Figure 2 The tensile strength test results of the BFRP bar with composite coating prepared in Example 1 after aging treatment, the BFRP bar with resin coating prepared in Comparative Example 1, and the BFRP bar (diameter 8 mm) without any treatment;

[0029] Figure 3 The results of the interfacial bonding strength test between the BFRP bars with a composite coating prepared in Example 2 after aging treatment, the BFRP bars with a resin coating prepared in Comparative Example 2, and the BFRP bars (with a diameter of 14 mm) without any treatment and concrete. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the description of the present invention, it should be understood that the directions or positions indicated by “upper” and the like are based on the directions or positions shown in the accompanying drawings, or are the directions or positions in which the product of the invention is usually placed when in use, or are directions or positions commonly understood by those skilled in the art. These directions or positions are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or component referred to must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as a limitation on the present invention.

[0032] Furthermore, the terms “first”, “second”, etc. are merely used for distinguishing descriptions and should not be understood as indicating or implying relative importance.

[0033] The order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0034] The present application provides a method for preparing an FRP bar with a composite coating, comprising the following steps:

[0035] S1, mixing a thermosetting resin, a resin curing agent or a resin initiator to obtain a resin coating;

[0036] S2, applying resin coating on the surface of FRP reinforcement;

[0037] S3. Coating the powder with volcanic ash activity on the surface of the resin coating, curing it to form a composite coating, and obtaining an FRP bar with the composite coating.

[0038] The preparation method of FRP bars with composite coating of the present invention, thermosetting resin is a polymer material with heat resistance, chemical corrosion resistance and high mechanical strength characteristics, which is used as a modified matrix of FRP coating, and is coated with powder with volcanic ash activity to form a volcanic ash activity-resin composite coating. When used as a steel bar substitute in concrete, the active ingredients in the volcanic ash active powder coated on the surface of the FRP bar undergo secondary hydration reaction with calcium hydroxide produced by hydration of cement clinker in concrete to generate low-alkalinity calcium silicate hydrate (CSH) and calcium aluminate hydrate, while promoting early hydration of cement through nucleation, and enhancing the compactness and interface bonding performance between FRP bars and concrete through micro-aggregate filling effect and particle morphology effect, which not only solves the corrosion degradation and interface debonding problems of the resin coating of FRP bars in high alkalinity concrete, but also enhances the interface bonding performance between FRP bars and concrete. The present invention realizes the enhanced design of corrosion resistance and interface bonding performance of FRP bar material system in concrete structure, and effectively improves the durability of FRP bars in concrete structure. This new type of FRP bar not only has unique properties in terms of corrosion resistance and interface bonding performance, but also meets the development needs of marine or coastal construction projects. At the same time, most industrial solid wastes have good volcanic ash activity, such as fly ash, silica fume, slag powder, etc., which has opened up new ways for the resource utilization of solid waste and has important practical significance and demonstration value for promoting industrial transformation and upgrading and promoting sustainable development.

[0039] In a specific embodiment of the present invention, through a comparative study of the durability test of uncoated, single resin coated BFRP bars and silica fume-resin composite coated BFRP bars at 25°C for 360 days, it was found that at the age of 360 days, the performance of the silica fume-resin composite coated BFRP bars only decreased by 8.8%, while the performance of the uncoated and resin coated bars decreased by 30.3% and 12.7%, respectively. More prominently, at 360 days, the performance of the silica fume-resin composite coating was 31.6% higher than that of the uncoated and 4.8% higher than that of the resin coating. In addition, by testing the interfacial bonding strength of BFRP bar concrete specimens immersed in 45°C simulated seawater at different ages, it was found that after 270 days of immersion test, the performance of the silica fume-resin composite coated BFRP bars increased by 1.67% compared with the initial value, while the performance of the uncoated and resin coated bars decreased by 16.68% and 9.39%, respectively. More prominently, at 270 days, the performance of the silica fume-resin composite coating was 19.32% higher than that of the uncoated and 24.64% higher than that of the resin coating. In summary, the FRP bars with composite coatings prepared by the present invention not only provide a new way to high-value utilization of industrial solid waste, but also have important practical significance for the construction of marine or coastal projects. Through material composite design, the comprehensive improvement of material durability and interface bonding performance is achieved, providing a solution with reference value for the development of FRP bars in seawater and sea sand concrete structure engineering.

[0040] In some embodiments, the powder having pozzolanic activity includes at least one of silica fume, fly ash, metakaolin, and slag powder.

[0041] In some embodiments, the thermosetting resin includes at least one of unsaturated polyester, vinyl ester, epoxy resin, phenolic resin, bismaleimide resin, and polyimide resin.

[0042] Specifically, the epoxy resin is bisphenol A epoxy resin E51.

[0043] In some embodiments, the resin initiator includes at least one of methyl ethyl ketone peroxide, dimethyl aniline, and diethyl aniline.

[0044] In some embodiments, the FRP tendons include basalt fiber reinforced composite tendons (BFRP tendons), carbon fiber reinforced composite tendons (CFRP tendons), glass fiber reinforced composite tendons (GFRP tendons), aramid fiber reinforced composite tendons (AFRP tendons), and the like.

[0045] Furthermore, the FRP bars used in the present invention refer to bars made of fiber reinforced composite materials (Fiber Reinforced Polymer, referred to as FRP), which can be used for the reinforcement and enhancement of seawater and sea sand concrete structures. The main components of FRP bars include high-strength fibers (such as glass fibers, carbon fibers or aramid fibers, etc.) and polymer matrices (such as epoxy resins, polyester resins or vinyl ester resins, etc.). In seawater and sea sand concrete, FRP bars have significant corrosion resistance advantages over traditional steel bars, can effectively resist chloride ion corrosion, improve the durability and service life of the structure, and are a very suitable material choice for marine engineering applications. However, studies have shown that the bonding performance between FRP bars and concrete is usually lower than that of traditional steel bars, because the surface of FRP bars is relatively smooth and lacks sufficient mechanical bite force and chemical bonding force, which may cause the bars to slip or interface damage when subjected to force, thereby affecting the integrity and bearing capacity of the structure; in addition, the high alkaline environment of concrete may chemically erode or degrade the matrix material (such as resin) of the FRP bars, especially under long-term service conditions. This effect may weaken the strength and durability of the FRP bars, thereby threatening the long-term performance stability of the structure. Therefore, when FRP bars are used in combination with concrete, they face compatibility issues such as insufficient interface bonding performance, differences in thermal expansion coefficients, and the influence of alkaline environments, which need to be solved by improving surface treatment, developing adhesives, and optimizing processes. The present invention fully demonstrates the application potential of volcanic ash powder in FRP bar coating modification, and provides an important theoretical basis and practical guidance for the development and utilization of FRP bars in marine or coastal engineering.

[0046] In some embodiments, the resin curing agent includes at least one of diethylenetriamine and triethylenetetramine.

[0047] In some embodiments, the mass ratio of the thermosetting resin, the resin curing agent or the resin initiator is (1-3):(1-3).

[0048] In some embodiments, the D50 particle size of the silica fume is 0.9-1.2 μm; the silica fume includes the following components by mass fraction:

[0049] SiO2 97.30%, CaO 0.30%, Al2O3 0.40%, SO3 0.83%, MgO 0.21%, K2O 0.26%, and the balance are inevitable impurities.

[0050] In some embodiments, the mass of the powder having pozzolanic activity is 2.5-4% of the mass of the resin coating.

[0051] In some embodiments, diethylenetriamine and triethylenetetramine are room temperature curing curing agents. Specifically, the curing temperature is 20 to 50° C. and the curing time is 1 to 30 hours.

[0052] In some embodiments, the thickness of the composite coating is 0.25 to 0.35 mm;

[0053] In some embodiments, a method for preparing a FRP bar having a composite coating comprises the following steps:

[0054] S1, mixing a thermosetting resin, a resin curing agent or a resin initiator to obtain a resin coating;

[0055] S2, applying the resin coating evenly on the surface of the FRP reinforcement by dipping, brushing, rolling, etc.;

[0056] S3. When the resin coating on the surface of the FRP bar is initially cured but has not yet reached a surface dry state (the surface of the resin coating is still sticky but will not sag under the action of gravity), the powder is evenly attached to the resin coating on the surface of the FRP bar by means of a powder spray gun (electrostatic spraying) or the like, forming a powder-resin composite coating FRP bar with volcanic ash activity.

[0057] Compared with untreated FRP bars, the present invention has the following advantages:

[0058] (1) By introducing the composite coating technology of powder and resin with volcanic ash activity, the volcanic ash active powder forms an active coating on the surface of FRP bars, which reacts with the cement hydration products in the concrete to generate more CSH gel. This gel can fill the micropores at the interface, reduce the porosity at the interface and prevent the intrusion of corrosive media, while improving the mechanical bite force and chemical bonding force between the interfaces;

[0059] (2) The volcanic ash effect produced by the powder with volcanic ash activity in concrete can effectively reduce the calcium hydroxide content at the interface or reduce the possibility of alkali-aggregate reaction, reduce the risk of erosion of FRP bars in the alkaline environment, and extend the service life of FRP bars;

[0060] (3) Most industrial solid wastes have volcanic ash activity (such as silica fume, fly ash, slag powder, etc.). These industrial solid waste powders with volcanic ash activity can be used as raw materials for coating modification, which broadens the path for solid waste resource utilization and meets the requirements of green building and sustainable development.

[0061] In summary, the technical method of enhancing the durability and interface performance of FRP bars in concrete structures involved in the present invention not only provides a new way for the high-value utilization of solid waste resources, but also has important reference value and practical significance in promoting the construction of marine or coastal projects. Through the composite design of materials, the durability and interface adhesion of FRP bars in concrete structures are improved, and new ways for the resource utilization of solid waste are broadened.

[0062] Based on the same inventive concept, the present invention also provides an FRP bar with a composite coating, which is prepared by the above-mentioned preparation method.

[0063] Based on the same inventive concept, the present invention also provides an FRP bar with a composite coating prepared by the above-mentioned preparation method or the use of the FRP bar with a composite coating in preparing concrete.

[0064] The following further describes the FRP bar with composite coating and its preparation method of the present application with specific examples. This section further describes the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0065] In the following embodiments, BFRP bars are used as base bars modified from FRP bars, and the BFRP bars are of diameters of 8 mm and 14 mm; among them, 8 mm is used for tensile strength test, and 14 mm is used for interface bonding strength test (8 mm bars are thinner, and are prone to breaking before interface failure occurs in the specimen when used for bonding test, resulting in failure to obtain complete interface bonding force-slip data, so 14 mm bars are selected); the BFRP bars are purchased from Jiangsu Nongchaoer Composite Materials Co., Ltd.

[0066] In the following examples, the resin used for the base coating on the surface of the BFRP bar specimen is bisphenol A epoxy resin (E51), and the corresponding initiator is diethylenetriamine, with a mass ratio of 1:1.

[0067] In the following examples, the powder with volcanic ash activity used is silica fume with a D50 of 0.9 μm. The silica fume includes the following components by mass fraction: SiO2 97.30%, CaO 0.30%, Al2O3 0.40%, SO3 0.83%, MgO 0.21%, K2O 0.26%, and the remainder is inevitable impurities.

[0068] Example 1

[0069] The present application provides a method for preparing a BFRP bar with a composite coating, comprising the following steps:

[0070] S1, mixing bisphenol A epoxy resin (E51) and initiator (diethylenetriamine) in a mass ratio of 1:1 to obtain a resin coating;

[0071] S2, applying the resin coating on the surface of the BFRP rib (with a diameter of 8 mm);

[0072] S3. As the resin coating on the surface of the BFRP reinforcement gradually solidifies, when it drips unnaturally under the action of gravity (usually 0.5h to 1h), the silica fume is evenly adhered and coated on the surface of the resin coating of the BFRP reinforcement by means of a powder spray gun (electrostatic spraying) (the mass of the silica fume is 3% of the mass of the resin coating), and solidified at room temperature (about 25°C). After 24h, the resin coating is completely solidified to obtain a BFRP reinforcement with a powder-resin composite coating with volcanic ash activity and a coating thickness of 0.25mm.

[0073] Example 2

[0074] The method for preparing the BFRP bar with a composite coating provided in this embodiment is the same as that in Embodiment 1, except that the diameter of the BFRP bar used is 14 mm, and the other process parameters are the same as those in Embodiment 1.

[0075] Comparative Example 1

[0076] This comparative example provides a method for preparing a BFRP bar with a resin coating, comprising the following steps:

[0077] S1, mixing bisphenol A epoxy resin (E51) and initiator (diethylenetriamine) in a mass ratio of 1:1 to obtain a resin coating;

[0078] S2. Apply the resin coating on the surface of the BFRP bar (diameter 8 mm), and cure it at room temperature (about 25° C.) for 24 hours to obtain a resin-coated BFRP bar with a coating thickness of 0.25 mm.

[0079] Comparative Example 2

[0080] This comparative example provides a method for preparing a BFRP bar with a resin coating, comprising the following steps:

[0081] S1, mixing bisphenol A epoxy resin (E51) and initiator (diethylenetriamine) in a mass ratio of 1:1 to obtain a resin coating;

[0082] S2. Apply the resin coating on the surface of the BFRP bar (diameter 14 mm), and cure it at room temperature (about 25° C.) for 24 hours to obtain a resin-coated BFRP bar with a coating thickness of 0.25 mm.

[0083] Performance Testing

[0084] Figure 1 The actual pictures are of the BFRP bar with composite coating prepared in Example 1, the BFRP bar with resin coating prepared in Comparative Example 1, and the BFRP bar (with a diameter of 8 mm) without any treatment.

[0085] Specifically, Figure 1The medium BFRP bar refers to the BFRP bar that has not been treated in any way, the resin-coated BFRP bar refers to the BFRP bar with a resin coating prepared in Comparative Example 1, and the silica fume-resin-coated BFRP bar refers to the BFRP bar with a composite coating prepared in Example 1.

[0086] The BFRP bar with a composite coating prepared in Example 1, the BFRP bar with a resin coating prepared in Comparative Example 1, and the BFRP bar (with a diameter of 8 mm) without any treatment were subjected to an aging test according to the American standard ACI 440.1R-15, comprising the following steps:

[0087] S1. The simulated pore solution of ordinary seawater and sea sand concrete used in this institute is prepared according to the American standard ACI 440.1R-15, which is composed of sodium hydroxide (2.4g / L, NaOH), potassium hydroxide (19.6g / L, KOH), calcium hydroxide (2g / L, Ca(OH)2) and artificial seawater (prepared according to ASTM D1141-98);

[0088] S2. The BFRP bars with composite coating prepared in Example 1, the BFRP bars with resin coating prepared in Comparative Example 1, and the BFRP bars without any treatment (with a diameter of 8 mm) are immersed in a simulated hole solution of ordinary seawater and sea sand concrete, and then placed in environmental chambers with different aging temperatures for aging tests until the specified age.

[0089] The tensile strength of the BFRP bar with composite coating prepared in Example 1, the BFRP bar with resin coating prepared in Comparative Example 1 and the BFRP bar (diameter 8 mm) without any treatment after aging treatment was tested to characterize its durability. Referring to the American standard ACI 440.1R-15, the test results are as follows: Figure 2 shown.

[0090] Figure 2 The uncoated BFRP bar (diameter 8 mm) does not undergo any treatment, the resin coated BFRP bar represents the resin coated BFRP bar prepared in Comparative Example 1, and the silica fume-resin coated BFRP bar represents the composite coated BFRP bar prepared in Example 1.

[0091] In the same manner as above, the BFRP bars with composite coating prepared in Example 2, the BFRP bars with resin coating prepared in Comparative Example 2, and the BFRP bars (diameter 14 mm) without any treatment were immersed in a simulated pore solution of ordinary seawater and sea sand concrete, and then placed in environmental chambers with different aging temperatures for aging tests until the specified age.

[0092] The interfacial bonding strength between the BFRP bars with composite coating prepared in Example 2 after aging treatment, the BFRP bars with resin coating prepared in Comparative Example 2, and the BFRP bars (diameter 14 mm) without any treatment and concrete was tested to characterize their interfacial bonding performance. Referring to the American standard ACI 440.3R-12, the test results are as follows: Figure 3 shown.

[0093] Figure 3 The uncoated BFRP bar (diameter 14 mm) does not undergo any treatment, the resin coated BFRP bar represents the resin coated BFRP bar prepared in Comparative Example 2, and the silica fume-resin coated BFRP bar represents the composite coated BFRP bar prepared in Example 2.

[0094] from Figure 2 It can be seen that through the comparative study of the durability test of the uncoated BFRP bar, the single resin coating BFRP bar in comparative example 1 and the silica fume-resin composite coating BFRP bar in example 1 under 25°C environment for 360 days, the silica fume-resin composite coating in example 1 showed significant performance advantages and excellent long-term stability in this experiment. In the initial stage (age 0 days), its tensile strength was 675.19MPa, which was 0.5% higher than that of the uncoated BFRP bar and 0.3% higher than that of the single resin coating BFRP bar in comparative example 1, and the performance of the three was close; as the age increased, the silica fume-resin composite coating in example 1 showed excellent anti-attenuation ability: at the age of 360 days, its tensile strength only decreased by 8.8%, while the tensile strength of the uncoated BFRP bar and the single resin coating BFRP in comparative example 1 decreased by 30.3% and 12.7%, respectively. More notably, at 360 days, the tensile strength of the silica fume-resin composite coating in Example 1 was 31.6% higher than that of the uncoated BFRP bar, and 4.8% higher than that of the single resin coating BFRP in Comparative Example 1. This result shows that the silica fume-resin composite coating not only effectively overcomes the performance degradation problem of the uncoated and single resin coatings, but also significantly improves the long-term performance, fully proving its superiority in durability and stability, and is a high-performance coating material with great potential.

[0095] from Figure 3It was found that by testing the interfacial bonding strength of BFRP bar concrete specimens immersed in simulated seawater at 45°C at different ages, the silica fume-resin composite coated BFRP bars in Example 2 showed significant performance advantages and superior long-term stability in this experiment. In the initial stage (age 0 days), its tensile strength performance was close to that of the uncoated BFRP bars, only 2.19% lower, and much better than the single resin coated BFRP bars in Comparative Example 2 (increased by 12.01%). As the age increases, the silica fume-resin composite coated BFRP bars in Example 2 show excellent anti-attenuation ability and performance improvement effect: at an age of 270 days, its performance is 1.67% higher than the initial value, while the uncoated and single resin coated BFRP bars in Comparative Example 2 decrease by 16.68% and 9.39%, respectively. More notably, at 270 days, the tensile strength of the BFRP bars with silica fume-resin composite coating in Example 2 was 19.32% higher than that of the uncoated BFRP bars, and 24.64% higher than that of the single resin coating BFRP bars in Comparative Example 2. This result shows that the BFRP bars with silica fume-resin composite coating in Example 2 exhibited superior interface bonding strength, corrosion resistance and long-term stability in the present invention, significantly improved the durability of the material, and overcame the performance attenuation problem of uncoated and single resin coatings, which not only provided technical guarantees for extending the service life of engineering structures and reducing maintenance costs, but also provided scientific basis and practical reference for the development and application of high-performance protective materials, and had important engineering application value and economic benefits.

[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a FRP bar with a composite coating, characterized in that: The following steps are involved: Mixing a thermosetting resin, a resin curing agent or a resin initiator to obtain a resin coating; Applying resin coating on the surface of FRP reinforcement; The powder with volcanic ash activity is coated on the surface of the resin coating, and solidified to form a composite coating, thereby obtaining an FRP bar with the composite coating.

2. The method for preparing the FRP bar with a composite coating according to claim 1, characterized in that: The powder with volcanic ash activity includes at least one of silica ash, fly ash, metakaolin and slag powder.

3. The method for preparing the FRP bar with a composite coating according to claim 1, characterized in that: The thermosetting resin includes at least one of unsaturated polyester, vinyl ester, epoxy resin, phenolic resin, bismaleimide resin and polyimide resin; And / or, the resin initiator includes at least one of methyl ethyl ketone peroxide, dimethyl aniline, and diethyl aniline; And / or, the resin curing agent includes at least one of diethylenetriamine and triethylenetetramine.

4. The method for preparing the FRP bar with a composite coating according to claim 1, characterized in that: The mass ratio of the thermosetting resin, the resin curing agent or the resin initiator is (1-3):(1-3).

5. The method for preparing the FRP bar with a composite coating according to claim 1, characterized in that: The FRP bars include any one of basalt fiber reinforced composite bars, carbon fiber reinforced composite bars, glass fiber reinforced composite bars, and aramid fiber reinforced composite bars.

6. The method for preparing the FRP bar with a composite coating according to claim 2, characterized in that: The D50 particle size of the silica fume is 0.9-1.2 μm; the silica fume includes the following components by mass fraction: SiO2 97.30%, CaO 0.30%, Al2O3 0.40%, SO3 0.83%, MgO 0.21%, K2O 0.26%, and the balance are inevitable impurities.

7. The method for preparing the FRP bar with a composite coating according to claim 1, characterized in that: The mass of the powder with volcanic ash activity is 2.5-4% of the mass of the resin coating.

8. The method for preparing the FRP bar with a composite coating according to claim 1, characterized in that: The curing temperature is 20-50°C; The thickness of the composite coating is 0.25-0.35 mm.

9. An FRP bar with a composite coating, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the FRP bar with a composite coating prepared by the preparation method according to any one of claims 1 to 8 or the FRP bar with a composite coating according to claim 9 in preparing concrete.